Design and evaluation of handheld clinical photoacoustic imaging system - Danial Asyraf Syahiran Rosli (2018)
Photoacoustic Imaging (PAI), or also known as optoacoustic imaging, is an imaging tool to study biological samples based on optical absorption contrast. It detects the acoustic wave generated by the absorption of pulsed light by the chromophores in the body such as hemoglobin. This has led to various uses in clinical medicine and preclinical research. One such use is the ability to image blood vessels. This is important, as the imaging of blood vessels is key in early detection of diseases. It is imperative for the system to be handheld, as it makes for clinical and preclinical use much easier. This study reports the design of a probe holder to integrate optical fibers and an ultrasound transducer together for use in PAI. Designs were made in various angles, using a 3D printer, from 0o up to 60o in order for us to better observe the effect of light delivery in different angles. The designs were made with easy to find materials and methods, and also taking less time to create. A phantom mimicking a human arm with a tube running across it to mimic a blood vessel was used to test and evaluate the efficacy of the design. The best angle for light delivery was also determined based on the result from the phantom experiment.